2012
DOI: 10.5455/msm.2012.24.198-202
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Activity on Cognition - Physiological Mechanisms

Abstract: The presumption that physical activity, i.e. exercise, as an independent and separated factor influences different aspects of cognitive mechanisms is substantially supported by the literature. The investigations of the influence of physical activity on cognitive functioning have offered several mechanisms which could explain this relationship. Physiological mechanisms including increased cerebral blood flow, changes in neurotransmitter release, structural changes in central nervous system and altered arousal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
1
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 53 publications
0
84
1
10
Order By: Relevance
“…53,54 Radical species upregulate antioxidant enzymes 55 and increase neurotropic factors, such as BDNF, VEGF, and IGF-1. 56,57 The Janus Face of exercise-induced oxidativenitrosative-inflammatory stress reflects a fundamental concept known as hormesis: 58 a toxicological term characterizing a biphasic dose-response encompassing a low-dose stimulation or beneficial effect and a high-dose inhibitory or toxic effect; 59 thus quantifying the impact of each exercise parameter on radical species may be a crucial step in determining the best exercise strategy for optimizing brain structure and function. Accordingly, people with higher baseline oxidative-nitrosative-inflammatory stress (e.g., older or diseased) might benefit from a different prescription of exercise with respect to this mediator of (mal) adaptation.…”
Section: Exercise and The Functional Regulation Of Cerebral Blood Flowmentioning
confidence: 99%
“…53,54 Radical species upregulate antioxidant enzymes 55 and increase neurotropic factors, such as BDNF, VEGF, and IGF-1. 56,57 The Janus Face of exercise-induced oxidativenitrosative-inflammatory stress reflects a fundamental concept known as hormesis: 58 a toxicological term characterizing a biphasic dose-response encompassing a low-dose stimulation or beneficial effect and a high-dose inhibitory or toxic effect; 59 thus quantifying the impact of each exercise parameter on radical species may be a crucial step in determining the best exercise strategy for optimizing brain structure and function. Accordingly, people with higher baseline oxidative-nitrosative-inflammatory stress (e.g., older or diseased) might benefit from a different prescription of exercise with respect to this mediator of (mal) adaptation.…”
Section: Exercise and The Functional Regulation Of Cerebral Blood Flowmentioning
confidence: 99%
“…However, physical exercise exerts different effects on the CNS. Several beneficial results demonstrated that physical exercise improves synaptic plasticity and cognition 13,28 , regulates the production and degradation of neurotransmitters 29,30 and increases angiogenesis 31 and neurogenesis 32 . Although the molecular mechanisms responsible for these events are not completely understood, there are strong evidences showing the exercise mediating the production and sensitivity to growth factors such as BDNF, IGF-1, IGF-2 and VEGF 1,28,32,33 .…”
Section: Neuroprotection Mediated By Physical Exercisementioning
confidence: 99%
“…Verantwortlich sind Zusammenhänge von körperlicher Bewegung mit der Synapsenbildung, der Ausschüttung von Vigilanz-fördernden Botenstoffen sowie die Sauerstoffversorgung des Gehirns (Gligoroska & Manchevska 2012;. Im Umkehrschluss hindert ständiges, ununterbrochenes Sitzen das Gehirn daran, optimale Leistung zu erbringen.…”
Section: Bewegungspausen In Der Hochschullehre: Evaluationsergebnisseunclassified